Treatment Of Scabies With 1% Gamma Benzene Hexachloride - Srinivas C.R; Satish Pai B; Jana Sukumar (Wolters Kluwer Medknow Publications, 1996)
We assessed the efficacy of 3 different treatment modalities with gamma benzene hexachloride (GBH) in an institutional outbreak of scabies. The 92 female inmates, between 5-18 years, in a state home with scabies and the supervisory staff were educated about the disease and treatment. As most inmates had secondary pyoderma, all were treated by a course of trimethoprim 80 mg; sulpha methoxazole 400 mg twice a day for 5 days. 250 lit of 1% GBH solution were prepared from 2.5 kg of GBH powder and were used for all the three treatment modalities. Forty-five girls were treated by GBH bath, each girl was allowed to soak in the tub for one minute and then allowed to dry; 34 girls were sprayed using a plastic hand spray and 23 were treated by paint brush application. Treatment was repeated after 1 week and reviewed after 2 and 6 weeks. On 1st visit, 4 girls of bath group showed few a symptomatic popular lesions over the hands and were retreated. All others were free of both symptoms and lesions. On second visit, all were free of lesions. All the three modes of drug delivery were effective. The bathtub offered privacy and it was quicker than both spraying and painting. However, the expense incurred per patient for bath was Rs.57 whereas it was only Rs.4 and Rs.5 for spray and paint brush application respectively.